Evaluation of Extensions of Sinonasal Malignancy by Clinical, Surgical & CT Scan Findings - Mahady, Ascif Al; Zaman, Fauzia; Anwar, Md Hasnat; Quayum, Mohammad Abdul; Atikuzzaman, Kazi; Sinha, Nanda Kishore (Bangladesh Journal of Otorhinolaryngology, 2023)
Background: Sinonasal malignancies are challenging not only from diagnostic view point but also from therapeutic aspects. Owing to the rarity of the lesions, delayed clinical presentations and poor prognosis there is lack of large experience. Objectives: Aim of this study is to assess Evaluation of extensions of sinonasal malignancy by correlating clinical and surgical findings with CT scan. Methods: A Cross Sectional study was carried out in the Department of Otolaryngology-Head and Neck Surgery, Sylhet M.A.G Osmani Medical College Hospital, Sylhet, from August 2019 to July 2021. A total 30 subjects were included in this study based on inclusion and exclusion criteria. A data collection form was designed and prepared including general characteristics of subjects and reviewed clinically, radiologically and surgically. All the data were compiled and sorted properly and the numerical data were analyzed statistically by using Statistical Package for Social Sciences (SPSS-26). The result was expressed as frequency and percentage and displayed with figure and table. Z proportion test, Spearman’s rho correlation coefficient test and Diagnostic accuracy test of clinical, CT and surgical finding were performed as applicable. For all comparisons p value of <0.05 was considered as significant. Results: In this study, CT findings was positively related with clinical and surgical findings. But this relation was strongly significant with surgical findings. In this study, clinical evaluation was 28.8% Sensitive and 100% Specific. Positive predictive value (PPV) was 100% and negative predictive value (NPV) was 9.1%. CT evaluation was 78.6% Sensitive and 100% Specific. Positive predictive value (PPV) was 100% and negative predictive value (NPV) was 25%. Surgical evaluation was 92.9% sensitive and 100% Specific. Positive predictive value (PPV) was 100% and negative predictive value (NPV) was 50%. Conclusion: It can be concluded that CT findings was directly correlated with clinical and surgical findings. But this relation was strongly significant with surgical findings. Bangladesh J Otorhinolaryngol 2022; 28(2): 171-179